Salafī Islam in Cambodia: Institution Building, Transnational Networks and Patterns of Competition in a Muslim-Minority Context - Pall, Zoltan (Die Welt des Islams, 2020)
After the departure of the United Nations and the restoration of the monarchy in 1993, Cambodia’s Muslim minorities became an important hub of transnational Muslim networks and movements, including the Salafī movement, which is increasingly influential. This article will examine how Salafism has inserted itself into Cambodian society and what limits there may be to its continued growth.